Hierarchization of a large chabazite crystal shaped with hydrogen difluoride and its catalytic performance in the MTO reaction - Marques, José Henrique [UNESP]; Pereira, Elen Maria Feliciano [UNESP]; Martins, Leandro [UNESP] (Elsevier, 2025)
Fully microporous SSZ-13 zeolites with CHA structure efficiently convert methanol to olefins (MTO) with high selectivity. Unfortunately, the microporosity that enables high selectivity is the same causing diffusion limitations for reactants and products. Modifying zeolite textures by post-synthetic treatment is an interesting strategy to overcome this issue. Herein, we synthesized a large acidic SSZ-13 zeolite crystal and then created a secondary porosity by treating it with an NH4HF2 solution. The strategy of using large crystals allowed for tracking the chemical and spatial coke evolution and the performance of catalysts in the MTO reaction. The NH4HF2 solution removed Si and Al atoms from the zeolite structure, mostly aluminum, creating mesopores. The formation of mesopores was accompanied by micropore degradation. The hierarchical zeolite performed better in the MTO reaction than the untreated zeolite. The tracking of coke during the reaction time revealed that the mesopores gave the catalyst a significantly higher lifetime despite coke growing into bulkier polyaromatic molecules with up to 4 aromatic rings. The spatial disposition of coke revealed by fluorescence confocal microscopy showed that the mesopores improve the utilization of the catalyst.
Keywords: Fluoride etching; Hierarchical zeolite; MTO; SSZ-13